Analysis of The Effect of Floating Net Cages on Reservoir Water Quality : (Case Study: Darma Kuningan Reservoir, Indonesia) - Syahrain, Azriel Albani; Rosiyanah, Dita; Putri, Nur Fieka; Farhan, Ohan (Jurnal Locus Penelitian dan Pengabdian, 2024)
The use of Darma Waduk is as a source of clean water and a place of fish cultivation in the form of net cages. The number of floating net cages that currently exist is 6521, and the number continues to increase quite significantly from the previous year. The existence of floating net cages affects water quality, while water quality is an aspect to be considered in water utilization. The study aims to analyze the impact of floating net cages on water quality and efforts to control the floating net cage population in Darma Waduk. The research uses a quantitative and qualitative approach, starting with surveys and interviews with floating net cage farmers and related services. Subsequently, water samples were taken, and the results of laboratory tests were analyzed using the Pollution Index (IP) method. The results of the calculation using the pollution index (IP) method at the first point (PDAM Intake Area) obtained a result of 4.14, at the second point (around the floating net cage area of the village of Cipasung) a value of 3.76, and at the third point (in the floating net cage village of Jagara) a score of 4.12. The results of the research showed that the water quality taken from the three points of the sample included light pollution when referring to the class I water quality standard according to PP No. 22 for 2021. However, the presence of household and agricultural waste also contributes to the pollution burden in the Darma Valley.